Ambivalensi Dakwah dan Intoleransi dalam Institusi Publik: Analisis SKB Tiga Menteri Perihal Atribut Pendidikan - Theresia Octastefani (Institut Agama Islam Negeri Bengkulu, 2021)
In the new normal period where all elements of the nation are struggling with the socio-economic condition's recovery due to Covid-19, the society must be surprised by the incident that occurred at State Vocational School of 2 Padang. In this case, a non-Muslim student felt forced by the school to wear the hijab which an Islamic attribute. As a result, there is the ambivalence of da’wah and intolerance in public institutions that are supposed to serve society fairly. The government through the Ministry of Education and Culture, the Ministry of Home Affairs, and the Ministry of Religion Affairs immediately responded by issuing a Joint Decree (SKB) of Three Ministers about educational uniforms and attributes. To analyze the ambivalence and pros cons of this phenomenon, this study uses a descriptive qualitative type. The results showed that chronologically, the time span between the case appearance and the SKB issuance was very fast, which was less than two weeks. The SKB reaps the pros and cons where on the one hand some parties think that this is an effort to secularize education, while on the other hand, some parties think that this SKB is very appropriate because Indonesia is already in an emergency situation of intolerance. However, regardless of the pros and cons, the issuance of the SKB was effective in guaranteeing the religious freedom of all education personnel and preventing ambivalence from da’wah which was distorted into intolerance.